(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
Language teaching has developed with numerous and different methods to ease the learning process and enhance learners ability to master communicative language skills. The Grammar-Translation Method (GTM) is one of the oldest and most significant approaches. This method originally comes from teaching classical languages such as Latin and Greek in past times, emphasizing mostly grammatical rules, vocabulary memorization, and translation based exercises. Although it has been criticized due to a lack of focus on oral and listening skills during the learning period, the GTM method has been widely used in many educational settings, especially where reading and writing are prioritized. It is primarily helpful to strengthen the formal style of language and appreciated among academics. This article explores the key principles, advantages, and drawbacks of GTM through comparing it with other existed language teaching methods, and discusses its accessibility with application in current education. Realizing the role of the GTM approach in classroom teachers, they can integrate it with other reliable methods to achieve further success in pedagogy.